The norms benefits awareness parameters for agent evaluation in norms adoption or rejection - Itaiwi A.-M.K.; Tang A.Y.C.; Ahmad M.S. (Institute of Advanced Scientific Research, Inc., 2023)
Agents within communities that have multiple agents tend to adopt implicit norms. They also enjoy unhindered mobility, moving among communities with relative ease so as to attain their objectives. Here, agents need to be provided with a tool for detection so as conform to situations in open communities. A smart agent needs to have the ability to independently assess its own level of awareness of norms' benefits, besides having the capability to discern between positive and negative norms while interacting in novel circumstances. If the agent does not succeed in identifying a particular community's norms accurately, it runs the risk of possible sanctions, or punishment in the case of transgressing prevailing norms. Conversely, if the agent were to identify the existing norms within a community, it would be able to reap the corresponding benefits, or at the very least, escape sanctions or penalties. A visiting agent that is armed with devices to identify norms of a particular society has the advantage of being able to adapt to shifts occurring within a particular setting, or to make adjustments to suit its own goals. This dissertation gives a conceptual framework for 'awareness of norms' benefits in open normative multi-agent societies. A fresh method to interpret and express an agent's behavior is presented here. Norms Adoption Ratio, Norms Yields, Norms Trust, and Norms Morality are the four elements that represent the agent's awareness of norms' benefits. By employing these criteria, agents can assess benefits of particular identified norms, following which they can ascertain whether these norms impact in a positive or negative way, thus helping them determine whether to embrace or discard a particular norm. 2018, Institute of Advanced Scientific Research, Inc.. All rights reserved.